Understanding Japan’s Civil Service System: Norms, Meritocracy, and Institutional Change - Zuliansyah P. Zulkarnain; Eko Prasojo (Indonesian Association for Public Administration, 2021)
This article aims to elucidate the tradition of Japan’s public administration emphasizing the civil service system. A number of studies explain the impact of the tradition (norms, values, and institutions), in shaping the process and result of public administration reform. By applying the historical institutionalism perspective, this study reveals how the legacy of the past, the tradition promoted by the Meiji Restoration, creates the new tradition of public administration. This study selects Japan as a typical case representing Asian developmentalists. The remarkable Meiji restoration marked the process of adoption and adjustment of the Germanic traditions in the bureaucracy modernization. Norm institutionalization has established the new norms and civil service system. The basic norms consist of legality, consensus, and seniority. It develops the